Design graphics : drawing techniques for design professionals - Koenig, Peter A. (Boston, Massachusetts : Prentice-Hall, 2012)
Design Graphics: Drawing Techniques for Design Professionals, Third Edition, combines in a single volume simple techniques and skills related to sketching, design-development, and the schematic or preliminary phase of design presentation. Emphasizing drawing as a mental as well as physical exercise, the text helps students draw designs on paper faster and easier, showing them how visual communication with clients can provide better, more economical design solutions. Practical, straightforward, and reader-friendly, Design Graphics provides more complete coverage of the basics, making concepts and techniques accessible to students with highly diversified educational and technical backgrounds.
Sketching -- 1. The basics -- 2. Line -- 3. Light -- 4. Texture -- Design drawing -- 5. Conceptual doodle/diagrams -- 6. Perspective drawing -- Drawing process. -- 7. One-point eyeball perspective -- 8. Two-point eyeball perspective -- 9. Overlay method -- 10. Entourage -- 11. Presentation.
Includes bibliographical references and index.
Keywords: ARCHITECTURAL DRAWING -- TECHNIQUE